2009
DOI: 10.1007/s00049-009-0005-y
|View full text |Cite
|
Sign up to set email alerts
|

Female sex pheromones in the host races and hybrids of the fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae)

Abstract: The three major pheromone components found in gland extracts of both rice and corn strain Spodoptera frugiperda virgin females were Z9-14:Ac, Z11-16:Ac and Z7-12:Ac, However, both the concentrations and relative proportions of the compounds varied significantly between strains as a function of female age and the time during the scotophase that the glands were extracted. The concentration of Z9-14:Ac found in the glands of hybrid females, coming from corn 9 rice and rice 9 corn crosses differed significantly, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
65
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 47 publications
1
65
0
3
Order By: Relevance
“…Because of their often tightly intermingled habitats and the ability of the rice strain to also utilize typical corn strain habitats to variable degrees, the two strains occur broadly sympatrically throughout South and North America (Meagher and Gallo-Meagher 2003;Prowell et al 2004;Nagoshi et al 2007;Machado et al 2008;Vélez-Arango et al 2008). No diagnostic morphological features have been described to distinguish these two strains, but they differ consistently in a number of physiological, developmental, and behavioral features (Pashley 1988;Pashley et al 1992Pashley et al , 1995Veenstra et al 1995;Meagher et al 2004;Groot et al 2008;Lima and McNeil 2009;Schöfl et al 2009). Using multilocus genotypes to examine the degree and directionality of hybridization between the fall armyworm strains in nature, Prowell et al (2004) concluded that up to 16% of the individuals sampled were potential hybrids, with many of those beyond the F 1 stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their often tightly intermingled habitats and the ability of the rice strain to also utilize typical corn strain habitats to variable degrees, the two strains occur broadly sympatrically throughout South and North America (Meagher and Gallo-Meagher 2003;Prowell et al 2004;Nagoshi et al 2007;Machado et al 2008;Vélez-Arango et al 2008). No diagnostic morphological features have been described to distinguish these two strains, but they differ consistently in a number of physiological, developmental, and behavioral features (Pashley 1988;Pashley et al 1992Pashley et al , 1995Veenstra et al 1995;Meagher et al 2004;Groot et al 2008;Lima and McNeil 2009;Schöfl et al 2009). Using multilocus genotypes to examine the degree and directionality of hybridization between the fall armyworm strains in nature, Prowell et al (2004) concluded that up to 16% of the individuals sampled were potential hybrids, with many of those beyond the F 1 stage.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage of the mating sequence, both males and females potentially can make a choice. In the fall armyworm, female pheromonal differences between the two strains have been described (Groot et al 2008;Lima and McNeil 2009), but their contribution to reproductive isolation remains to be tested. Male S. frugiperda possess eversible abdominal hair pencils and use them when approaching females (G. Schöfl, personal observation), but a male pheromone has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Strain-speciÞc differences in mating behavior have been observed, most notably in the timing during scotophase of female calling, male calling, and copulation (Pashley et al 1992, Schoß et al 2009). Recently, strain differences in the sex-pheromone emitted by the female were found, although there was disagreement about the speciÞc components involved (Groot et al 2008, Lima andMcNeil 2009). However, these mating barriers are not absolute, as hybridization between the two strains can be induced in the laboratory (Nagoshi et al 2006a(Nagoshi et al , 2008a, and it is estimated that Ϸ16% of the fall armyworm collected from Louisiana, Florida, Puerto Rico, Guadeloupe, and French Guiana from 1990 to 1992 were derived from interstrain hybridization (Prowell et al 2004).…”
mentioning
confidence: 99%
“…Attempts to Þnd reproducible strain differences under controlled laboratory conditions have had some notable, but limited success. The two strains appear to differ in the timing of important aspects of mating behavior and in the components of the female sex pheromone (Pashley et al 1992, Groot et al 2008, 2010Lima and McNeil 2009;Schoß et al 2009;Groot et al 2010). There are also reports of strain differences in ovipositional substrates, developmental time and viability on various hosts, and mating preferences, though these have often not been in agreement (Pashley and Martin 1987, Whitford et al 1988, Quisenberry 1991, Veenstra et al 1995, Meagher et al 2004.…”
mentioning
confidence: 99%